EFEKTIVITAS PEMANFAATAN LAHAN UNTUK BUDIDAYA TANAMAN PANGAN (PADI SAWAH) DI KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - ", Astriati; Harahap, Tuti Khairani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
:Effectiveness of Land Use for Food Crops ( paddy Rice ) in the Districtof Rokan Hulu Rambah Samo. This research background by the program designedby the Government of Rokan Hulu to realize the vision of the year 2013 " RokanHulu as rice self-sufficiency " . However , it seems this plan can not be realized withgood results . To achieve these targets , the Government of Rokan Hulu through theDepartment of Food Crops and Horticulture initiative to organize the cultivation offood crops of rice ( paddy rice ) . However , can not operate effectively due to someobstacles on the ground .The purpose of this study was to determine the effectivenessof the use of land for cultivation of food crops (paddy rice) in District Rambah Samoand to determine the factors that hinder the effective use of land for cultivation offood crops (paddy rice ) in District Rambah Samo regency Rokan Hulu .Keywords: Effectiveness, benefit, and political will.